2019
DOI: 10.3390/cancers11081174
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antibiotics and Risk of Cancer: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: The association between antibiotic use and risk of cancer development is unclear, and clinical trials are lacking. We performed a systematic review and meta-analysis of observational studies to assess the association between antibiotic use and risk of cancer. PubMed, the Cochrane Library and EMBASE were searched from inception to 24 February 2019 for studies reporting antibiotic use and subsequent risk of cancer. We included observational studies of adult subjects with previous exposure to antibiotics and avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
76
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 53 publications
0
76
0
1
Order By: Relevance
“…Relevant publications have raised the hypothesis that certain drugs are associated with carcinogenesis [ 32 , 33 ] and that the regular use of antibacterial drugs may be associated with cancer development [ 34 ]. According to a recent meta-analysis of 25 observational case–control or cohort studies, there is moderate evidence that the prolonged or excessive use of antibiotics during a person’s life is associated with a slight increased risk of various types of cancers [ 35 ]. Besides, a nested case–control study for 15 common malignancies revealed that a recurrent exposure to certain antibiotics frequently used in the community may be associated with cancer risk in specific organ sites [ 35 , 36 ].…”
Section: Cancer Risk With Antibioticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Relevant publications have raised the hypothesis that certain drugs are associated with carcinogenesis [ 32 , 33 ] and that the regular use of antibacterial drugs may be associated with cancer development [ 34 ]. According to a recent meta-analysis of 25 observational case–control or cohort studies, there is moderate evidence that the prolonged or excessive use of antibiotics during a person’s life is associated with a slight increased risk of various types of cancers [ 35 ]. Besides, a nested case–control study for 15 common malignancies revealed that a recurrent exposure to certain antibiotics frequently used in the community may be associated with cancer risk in specific organ sites [ 35 , 36 ].…”
Section: Cancer Risk With Antibioticsmentioning
confidence: 99%
“…According to a recent meta-analysis of 25 observational case–control or cohort studies, there is moderate evidence that the prolonged or excessive use of antibiotics during a person’s life is associated with a slight increased risk of various types of cancers [ 35 ]. Besides, a nested case–control study for 15 common malignancies revealed that a recurrent exposure to certain antibiotics frequently used in the community may be associated with cancer risk in specific organ sites [ 35 , 36 ]. Since antibiotics have no known direct carcinogenic effect, the main hypothesis for the increased cancer risk focuses on their influence on the composition of the human microbiome, which involves the bacteria that compose the microbiota, their genes, metabolites and interactions with one another, as well as with their host collectively, including the immune system [ 4 , 37 ].…”
Section: Cancer Risk With Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations